Phytochemical Constituents and GC-MS Profiling of the Whole Plant Ethanol Extract of Thesium viride Hill and its Oral Toxicity in Balb/C Mouse Model - Mustapha, F. J.; Ella, E. E.,; Luka, S. A.,; Wada, Y. A. (UMYU Journal of Microbiology Research)
Thesium viride Hill, a member of the Santalaceae family, treats several ailments. However, few pharmacological investigations have been done to ascertain its folklore usage. The present study evaluated the presence of phytochemical constituents and Gas Chromatography-Mass Spectroscopy profiling of the whole plant extract of Thesium viride and its oral toxicity in the Balb/c mouse model. The whole plant-dried sample was collected from Zaria local government, Kaduna State, Nigeria, and 400 grams of the pulverised plant was extracted by the Soxhlet method using different solvents. Phytochemical screening and GC-MS analyses of the whole plant ethanol extract were done according to standard procedures. Acute oral toxicity studies of the extracts were carried out on BALB/c mice weighing 17-23g following recommendations from the OECD. The phytochemical analysis of Thesium viride whole plant extracts showed the presence of cardiac glycosides, carbohydrates, flavonoids, tannins, saponins, steroids, triterpenes, and alkaloids. In addition, the GC-MS analysis of the ethanol extract of Thesium viride revealed the presence of thirty-four bioactive compounds, the major ones being Bis (2-ethylhexyl) phthalate, cis-13-Octadecenoic acid, trans-13-Octadecenoic acid, n-Hexadecanoic acid, 9-Octadecenoic acid (Z), and Diethyl Phthalate with peak areas (concentrations) of 34.44%, 29.75%, 4.18%, 3.60%, 2.62%, and 2.01% respectively. The median lethal dose (LD50) for acute toxicity studies of different fractions of Thesium viride on Balb/c mice was greater than 5000 mg/kg. The study concludes that the whole plant extract of Thesium viride is rich in phytoconstituents with pharmacological prospects. The extract is practically non-toxic and safe when administered orally in mice.